POLA PENDAYAGUNAAN ANGKATAN KERJA DI DAERAH PERDESAAN - NFN Daliyo (Jurnal Kependudukan Indonesia, 2009)
The aim of this article is to analyze the patterns of labour utilization in Temanggung Regency rural areas. The study shows that there are significant differences oflabour utilization between two typological villages in the rural areas ofTemanggung Regency. The labour force which can be categorized adequately utilized in the lowland area was higher than in the highlands area (70% and 50%). Generally the unemployment rate in the lowland area was lower than in the highlands area. The labour force which categorized as underutilization by hours was lower in the lowland area than in the highlands area. The similar pattern was also found among underutilization of labour force by hours and income. Generally, it can be concluded that the utilization of labour force in the low land villages were higher than in the highlands villages. The main source of information for this study came from Disguised Unemployment in Temanggung Regency Rural Areas, in 2008.Keywords: Employment, Empowerment, Rural Area